Analysis of Mutational Profiles of SARS-CoV-2 Structural and Non-Structural Proteins with Emphasis on Spike Protein Variants - Bhattacharyya, Saptarshi (Trends in Sciences, 2022)
SARS-CoV-2 has very recently posed a potential threat to humanity due to its very rapid rate of mutations and repairing mechanism. The spread of this virus is considered to have occurred in Wuhan, China in December 2019. Characterized by high rates of transmission, the virus is constantly evolving towards attaining higher rates of stability and transmissibility through acquiring mutations in its genome. Therefore, this study aims to analyse the mutational profiles of SARS-CoV-2 isolates. Analysis of the mutational profiles in individual SARS-CoV-2 proteins will allow us to look into the rates of mutations associated with each protein. Frequently mutated residues have been identified in this research by aligning 688 SARS-CoV-2 nucleotide sequences, which were downloaded from NCBI (National Center For Biotechnology Information) repository. Further, mutational frequencies of these mutated residues have been studied, which is instrumental in identifying the proteins that are resistant to changes, as well as the ones that have a greater proclivity towards incorporating mutations. HIGHLIGHTS The rates, frequencies and proclivities of mutation (w.r.t each protein) in SARS-CoV-2 were analyzed to facilitate vaccine development , supplemented with a phylogenetic tree (w.r.t spike protein) D614G mutation (frequency of more than 40 %) is crucial in imparting greater viral stability and transmissibility Both, at gene and protein level, number of mutations per 100 bases are high in Nucleocapsid , ORF3a and ORF8 Envelope and Membrane proteins have housekeeping functions GRAPHICAL ABSTRACT